From decentralization to re-centralization: lessons learned from Vietnam's rapid reversal in the financing of the Expanded Program on Immunization - Khanh Phuong Nguyen; The Due Ong; Xinyu Zhang; Tra My Do; Thi Quynh Trang Do; Shenglan Tang (The Lancet Regional Health. Western Pacific)
Summary: Ensuring sufficient financial resources for improving effective and efficient procurement of vaccines was highlighted by the Immunization Agenda 2030, which is particularly challenging for middle-income countries (MICs) that are ineligible for support from Gavi, the Vaccine Alliance. In response to the broader decentralization of the governance system and decreased international development aid, the central government of Vietnam decentralized the responsibility of financing the Expanded Program on Immunization (EPI) to provincial governments in 2023 but rapidly reversed it considering its following negative consequences, for example, severe vaccine stockouts and the largest decline in childhood immunization coverage in over 20 years. This paper analyzed the consequences closely linked to decentralization in Vietnam, the underlying reasons, and lessons for other MICs. To avoid recurrence, MICs should ensure the primary role of the central government in EPI financing and management, improve the local management capacity, and allocate more resources toward less-developed areas to narrow the intra-country disparities.